MSG – Manfaat Micin untuk Tanaman Padi (Mantap) sebagai Pangan yang Bebas Bahan Kimia dan Ramah Lingkungan Guna Menjaga Kesehatan Masyarakat Menuju Indonesia Berkemajuan - Bela, Dinda Velita; Latifah, S. (Seminar Nasional Lahan Suboptimal, 2019)
Bela DV, Latifah S. 2019. MSG-benefits of micin for rice (steady) plants as a food that is chemical-free and environmentally friendly to maintain public health towards a progressing Indonesia. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 502-507. Palembang: Unsri Press.Indonesia is one of the countries that has the largest population in the world, 260,580,739 people whose staple food is rice (cooked rice from rice). Over time, the need for rice is increasing, as a result farmers take a way out by using chemicals to produce maximum harvest, even though the use of chemicals is not good for the health of the body, especially if consumed long and excessive. But in reality in various regions the use of chemicals as fertilizers is still very high. Thus, one way to reduce the use of chemicals in rice plants is by using MSG (Monosodium Glutamate) as a maximum fruit-producing auxiliary material. The content of compounds in MSG can increase water content during the summer or dry and is able to nourish the development of plants. So that MSG can prevent the occurrence of water resistance, fertilize plants and make plants look fresh with greener leaves, dense and healthy rice. So with the use of MSG, besides being environmentally friendly, rice is also free of chemicals.Keywords: environmentally friendly, MSG, rice growth